2005
DOI: 10.1029/2005gl022427
|View full text |Cite
|
Sign up to set email alerts
|

Observed positive feedback between the NAO and the North Atlantic SSTA tripole

Abstract: [1] NCEP-NCAR reanalysis data from 1948 to 2001 are used to examine the relationship between the North Atlantic Oscillation (NAO) and the North Atlantic sea surface temperature anomaly (SSTA) tripole. It is demonstrated that the atmospheric anomalies associated with NAO produce tripole-like sea surface temperature (SST) anomalies; in turn, the SSTA tripole produces NAO-like atmospheric anomalies. Therefore, a positive feedback between the NAO and the SSTA tripole is suggested. The results are statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
78
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 17 publications
9
78
0
Order By: Relevance
“…The KOElike SST anomalies can provide anomalous forcing to the regional climate especially when the atmosphere has reduced its internal variability during spring. Most recently, Pan (2005) demonstrated that there is a positive feedback between the NAO and the tripole pattern of the SST anomalies in the North Atlantic, which supports our results on the coupling between SST anomalies and the overlying atmosphere in the extratropics. Miller and Schneider (2000) have suggested that the response of the western Pacific SST to decadal forcing by the Aleutian Low is a 2-5 year lagged KOE SST pattern.…”
Section: Summary and Discussionsupporting
confidence: 80%
“…The KOElike SST anomalies can provide anomalous forcing to the regional climate especially when the atmosphere has reduced its internal variability during spring. Most recently, Pan (2005) demonstrated that there is a positive feedback between the NAO and the tripole pattern of the SST anomalies in the North Atlantic, which supports our results on the coupling between SST anomalies and the overlying atmosphere in the extratropics. Miller and Schneider (2000) have suggested that the response of the western Pacific SST to decadal forcing by the Aleutian Low is a 2-5 year lagged KOE SST pattern.…”
Section: Summary and Discussionsupporting
confidence: 80%
“…The heat flux anomalies associated with the NAO can enhance or diminish the impact of ENSO, depending on the NAO phase (e.g., Grö tzner et al 1998;Giannini et al 2001b;Czaja et al 2002). It has been demonstrated that atmospheric anomalies associated with NAO produce tripolelike SSTA in the North Atlantic (Deser and Timlin 1997;Marshall et al 2001;Pan 2005). As the tropical Atlantic signature of the NAO-forced SST tripole in the North Atlantic, the NTA SST variability is also modulated by the NAO.…”
Section: Influences Of the Nao On The Nta Wpbmentioning
confidence: 96%
“…A number of factors contribute to the less distinct nature of the NAE teleconnection. Transient eddy feedbacks and air-sea interactions are important (Watanabe and Kimoto 1999;Pan 2005), with North Atlantic SSTs playing a possible role in delaying the response to ENSO or modifying it to project onto the North Atlantic Oscillation (Herceg-Bulić and Kucharski 2012). A more general challenge for simulating ENSO impacts is the chaotic nature of the midlatitude atmosphere, which reduces the signal-tonoise ratio and limits predictability, also giving rise to uncertainty on what the real-world teleconnection actually is (Deser et al 2017).…”
mentioning
confidence: 99%